Usability Testing pada Aplikasi Mobile SnapChat Menggunakan System Usability Scale - Azzahra, Syifa; Khadijah, Khadijah; Sunarsih, Sunarsih (Jurnal Teknologi dan Manajemen Informatika, 2024)
The Snapchat application is a mobile-based social media platform for interacting withothers through messages, photos, or videos. Although the Snapchat application was previously booming in Indonesia, its usage has declined over time. Therefore, the usability of the Snapchat application needs to be evaluated to determine how easy the application and its features are to use. This research aims to conduct usability testing on the Snapchat mobile application by measuring three aspects: effectiveness, efficiency, and satisfaction. The effectiveness and efficiency aspects are evaluated through task scenario testing, while the satisfaction aspect is evaluated using the System Usability Scale (SUS). The respondents involved in this usability testing consist of 5 new users and 5 long-time users of the Snapchat application. The evaluation results obtained were then used as a basis for formulating recommendations for interface design improvements in the form of a prototype, which was subsequently re-evaluated in the same manner as the previous evaluation. The evaluation results after the interface design improvements showed an increase in the effectiveness aspect by 12.50%, the efficiency aspect by 19.54%, and the SUS score by 18.75.